A comparative study on eid advertisement video through corporate Youtube channels and audience engagement in Malaysia - Shazleen Mohamed; Wardatul Hayat Adnan; Ahmad Syazwan Syuwari Nordin; Mohd Fadly Khamis (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the trend of Eid-related video advertisements in Malaysia on online streaming platforms like YouTube, as focusing on major corporate channels such as Petronas, TNB, Malaysia Airlines, and Telekom Malaysia. Thus, the aim of the study is to explore the trend of Eid advertisements and Malaysian audience engagement through corporate video on YouTube Channel. Notable differences emerged in how each company portrayed these values, showcasing unique approaches to brand representation. Despite the commonality in values, the varied portrayal methods indicated distinct brand identities for each organisation. The analysis was conducted using content analysis through viewing the Eid advertising video which emphasised the importance of crafting a brand image within the Eid-themed video content to resonate and be memorable among viewers. Findings shows that while companies align on shared values for Eid advertisements, the way these values are communicated plays a crucial role in shaping the brand's image and audience engagement. Consistent and respectful representation of shared values building trust towards the audiences. Meanwhile, broadcasters must ensure that the advertisements they air are culturally sensitive and align with the values of the audience.